The benefit of fodder legumes as dairy feeding source for reducing greenhousegas emissions of modelled farms - Karin Weggler; Elisabeth Gerster; Jörg Messner (Frontiers in Sustainable Food Systems)
Agriculture and the dairy sector in particular are required to reduce greenhousegas (GHG) emissions. Fodder production is the third major source of GHG emission in dairy production. The use of small seeded legumes as major fodder could possibly reduce this source of GHG emissions. Since fodder requirements and fodder production are intertwined we used a modelling approach. The GHG emission of four model dairy farms were analyzed using the “calculation standards for GHG balances for single agricultural farms” (BEK). The farms differed in feeding rations and crop production but contained an equal number of dairy cows with similar milk productivity. The major difference was the source of protein used in the feeding strategy, which was a) rapeseed-extraction meal, b) clover-dominated ley silage c) mixed using both previous elements and d) high yielding clover-dominated leys. The landuse based GHG emissions were markedly reduced in the legume-fodder based compared to oilseed-rape based farms and intermediate for farms with a mixed feeding strategy. These reductions in GHG emissions were distinctly influenced by modelled soil humus-C accumulation. The reductions in landbased GHG emissions due to clover-ley as major fodder were notable, with emissions being decreased by generally 164,544 kg CO2e farm−1 and up to 191,562 kg CO2e farm−1 equal to 70 to 82%, compared to the rapeseed-extraction meal based farm. These substantial landuse based reductions in GHG emissions were close to half the amount arising from enteric fermentation of 100 cows from these model farms. When landuse and animal husbandry based GHG emissions are combined then GHG emission per hectare could be reduced by 36% in the legume dominated compared to the conventional farm. The product based GHG emission for milk production was also markedly reduced by 24–27% equal to 0.19–0.22 kg CO2e ECM−1 using the same comparisons. A clover dominated feeding strategy also reduced the N-purchases of farms but increased land requirement for fodder production and reduced available land for tradeable crops. Nevertheless, a feeding strategy including clover dominated leys could be an easily implemented tool to substantially reduce GHG emissions of dairy farms.